Investigation Into Environmental Selenium and Arsenic Levels and Arseniasis Prevalence in an Arsenic-Affected Coal-Burning Area - Bai, Ai-Mei; Li, Qian; Li, Yue; Fan, Zhong-Xue; Li, Xiao-Qian; Tan, Wen-Hong; Cao, Dong-Yuan; Kang, Yi-Jun (Frontiers in Nutrition, 2022)
Objective: To explore whether selenium concentration is correlated with arseniasis in a high arsenic-containing coal area in south Shaanxi Province, China. Methods: Epidemiological investigation was conducted among 50 arsenic poisoning patients in Ziyang County, a high arsenic and selenium area. Fifty healthy subjects were selected in a non-endemic arsenic poisoning area. The subjects in the high-arsenic coal area were diagnosed as normal subjects, and suspicious, mild, moderate, severe arsenic poisoning patients. Local coal, water, soil, corn, pepper samples, as well as hair, blood, urine samples of subjects and patients were collected for testing the arsenic and selenium contents. Results: The contents of arsenic and selenium in coal, soil, pepper and hair samples except selenium contents in corn from Ziyang County were significantly higher than those in the control area. The hair arsenic content in Ziyang County was positively correlated with arsenic poisoning, while hair and urine selenium contents were negatively correlated with arsenic poisoning. Conclusion: The content of selenium in the body is negatively correlated with the degree of arsenic poisoning, indicating that selenium may accelerate the metabolism and decumulation of arsenic and antagonize arsenic’s function.